The antecedents of subjective well-being of Javanese paramedics: The indigenous study - Sahrah, Alimatus; Yuniasanti, Reny (Jurnal Pendidikan Bitara UPSI, 2020)
Regarding the Indonesia government’s program namely leading to the Healthy Indonesia to the year 2025, a study in 2016 showed that the paramedics with the Javanese ethnic background demanding increase on welfare. Whereas, the Javanese paramedics were well-known to hold the role of harmony which tended to avoid conflict and they are obedient and tolerant. Subjective wellbeing (SWB) becomes one of the important factors that can determine and increase the welfare. It is very important to investigate the antecedents of SWB among Javanese Paramedics to enhance their performance. This research is a qualitative study with interview to 15 Javanese paramedics that consisted of 11 woman and 4 man paramedics in the Health Office of Yogyakarta. The interview transcript was classified by three academics of psychology who understood the Javanese culture. Then, they were calculated to notice which antecedents that would have the big effect. The results indicated that there was difference between the antecedents of SWB in the previous research and the antecedents of SWB in Javanese Paramedics. The antecedent subjective well-being is divided into four categories, i.e. physical, psychics, social and religiosity. Woman tends more on instrumental values while man tends more on terminal values. This result will help the Health Department of Yogyakarta to make an appropriate intervention for their paramedics to increase SWB.